Comparison of Behavioural Effects of Venlafaxine and Imipramine in Rats - Nowakowska, Elzbieta; Kus, Krzysztof; Chodera, Alfons (Arzneimittelforschung, 2003)
The experiments outlined in this paper examined the effects of the novel antidepressant venlafaxine (VEN) (CAS 9930-78-4) in several behavioural and memory tests in comparison with the classic antidepressant imipramine (IMI) (CAS 113-52-0).The tests were carried out on male Wistar rats of about 200 g. The drugs were administered orally 30 min before the tests during 14 days. The aim of the locomotor activity test was to select the doses without influence on the motility of the animals and active at least in two behavioural tests. Such dose was 20 mg/ kg b.w. for both drugs − VEN and IMI. In the immobility test, which reflects antidepressant drug activity, the following differences were found: VEN shortened immobility time (IT) on days 1 and 7 (no activity on day 14), whereas IMI shortened IT on days 7 and 14 and displayed no activity on day 1. In the two-compartment exploratory test both drugs displayed distinct anxiolytic effect on days 1 and 7, yet on day 14 only IMI was still active. In the maze test only VEN shortened food finding time on day 1, on day 7 and on day 14 during chronic treatment. IMI was inactive in the maze test.The authors conclude that the general pattern of VEN activity is similar to that of IMI, but in some tests, especially in the memory test, the new drug is superior to IMI.
Keywords: Antidepressants; CAS 113-52-0; CAS 9930-78-4; Imipramine, behavioural effects, rats; Venlafaxine, behavioural effects, rats